SHARIAH COMPLIANCE, ISLAMIC CORPORATE GOVERNANCE, AUDIT COMMITTEE, AND SHARIA SUPERVISORY BOARD EFFECT ON FRAUD - Fatkhur Rohman; Syaharani Noer Fathia; Widya Rizki Eka Putri; Ayu Dwiny Octary; Rona Majidah (Faculty of Economics and Business, 2026)
This study aims to examine the influence of Shariah Compliance, Islamic Corporate Governance (ICG), Audit Committee, and Sharia Supervisory Board (SSB) on fraud in Indonesian Sharia banking. This research uses a quantitative approach with panel data analysis. The sample consists of 13 Islamic commercial banks in Indonesia observed during the period 2022–2024. Shariah compliance is measured using the Islamic Income Ratio, Profit Sharing Ratio, and Zakat Performance Ratio. Panel data regression analysis was employed using the Common Effect Model (CEM) as the selected estimation model. The findings show that the Profit-Sharing Ratio and Sharia Supervisory Board have a significant effect in increasing fraud, indicating that these variables are associated with a higher occurrence of fraud. Meanwhile, the Islamic Income Ratio, Zakat Performance Ratio, Islamic Corporate Governance, and Audit Committee do not have a significant effect on fraud. The results suggest that several governance and compliance mechanisms in Islamic banks have not yet effectively strengthened fraud prevention. The effectiveness of profit-sharing mechanisms and the supervisory role of the Sharia Supervisory Board require further attention. This study is limited by the short observation period and small sample size. However, it contributes to the literature by providing empirical evidence on the role of Shariah compliance and governance mechanisms in influencing fraud in Islamic banking, offering insights for regulators and banking practitioners to improve fraud prevention.